Marriage, Divorce, and Remarriage: A Review of the Relevant Religious Literature, 1973–1983 - Barber, Cyril J. (Journal of psychology and theology, 1984)
With the rise of divorce, even among Christians, there has come about a corresponding increase in the number of Christians entering second marriages. This has posed a dilemma for ministers and church boards, pastoral counselors and Christian therapists. Widely divergent views are commonly encountered. The question brought before those in the helping professions is, Can divorced people remarry? Does Scripture contain principles as well as precepts that may be applied to situations in which a person finds himself or herself married to an alcoholic, a drug user, a homosexual or lesbian, or to a violent person whose mental, emotional and physical abuse makes life intolerable, or to someone who violates the sanctity of marriage with repeated promiscuity? This article investigates the viewpoints of leading writers on the subject of marriage, divorce and remarriage and presents in summary fashion the rationale of each writer for the viewpoint espoused.